Modeling bioconvective mixed convection of non-newtonian nanofluids using finite difference approach: A Jeffrey fluid model - Khan, M. Ijaz (Tribology international, 2025)
The bioconvective mixed convection flow has engineered significant applications in various industrial processes, biotechnology systems and biomedical engineering. The objective of current analysis is to analyze a two-dimensional bioconvective flow of non-Newtonian nanofluid in presence of mixed convection effects. The flow is subject to stretched cylinder. The Jeffrey fluid model is retained in order to evaluate the rheological aspects of non-Newtonian material. The motivated bioconvective problem addresses the heat and mass transfer impact in complex systems. The numerical simulations are performed with implementation of finite difference method (FDM). Physical aspects behind variation of parameters are graphically intended. It has been predicted that fluid velocity enhances due to Grashof number and buoyancy ratio parameter. The microorganisms profile declined due to higher Peclet number. The findings are particularly relevant to the design of nanofluidic heat exchangers, bio-convective cooling technologies, microbial fuel systems, and MHD-based polymer processing devices.